Prevalence of human immunodeficiency virus — hepatitis B virus co-infection amongst adult patients in Mahalapye, Ngami, Serowe, Botswana: a descriptive cross-sectional study - Azhani Mandiwana; Stephane Tshitenge (South African Family Practice, 2017)
Background: About 37 million people are living with human-immunodeficiency-virus (HIV) worldwide, with 2.6 million co-infected with the hepatitis B virus (HBV). HBV infection causes 650 000 deaths annually worldwide. Botswana has a high prevalence of HIV and a growing population of patients on highly active antiretroviral therapy (HAART). This study aimed to determine the prevalence of HIV–HBV co-infection amongst HAART eligible adult patients in some rural settings in Botswana.